Dans la solitude des autres : pour une histoire sociale et politique du concept de solitudo au Moyen Âge - Gabriel Castanho (Bulletin du Centre d’Études Médiévales d’Auxerre)
This article is a study of the relationship between the word solitudo and the definitions attached to it during the Middle Ages. Our investigation begins with the establishment of a vocabulary of solitude to specify the particularities of the semantic field studied. It will allow us to notice that the medieval solitude, unlike today, is understood, above all, as a space defined by actions. The following step of our research will propose a comparison between the meanings used in various types of documents, what will reveal a process of monopolization and ecclesiastical regulation of isolation. Finally, two major conclusions will be imperative : 1) the medieval solitude aims at balancing, between utopia and ideology, the antisocial tensions around the religious desire of abandonment of the world ; 2) the importance of the concept of solitude for the political history itself.